2016
DOI: 10.21608/ejhc.2016.195280
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students' emotional intelligence and their preferred conflict resolution strategies

Abstract: Background Nursing is a profession affected by conflict and stress, having essential EI skills can be helpful in handling stress and conflict Aim to investigate the influence of EI on nursing students' conflict resolution strategies Design A cross-sectional analytical study was used in this study Subjects 363 nursing students from first and fourth year Setting Faculty of Nursing at Ain-Shams University at Cairo in Egypt during the academic year 2013-2014. Tools Emotional Intelligence was measured using BarOn E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Several studies highlighting the importance of this topic have evaluated the EI level in nursing students and indicated that variability exists in the EI levels of nursing students in various nations and cultural contexts. While few studies have reported low levels of EI (Fakhry & El-Azeem, 2016 ; Faye et al, 2011 ), the research majority found moderate to high EI levels (Albagawi, 2018 ; Almegewly et al, 2022 ; Beauvais et al, 2011 ; Mahmoud et al, 2013 ). The observed variability can be attributed to individual characteristics, cultural values, and educational system variations.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies highlighting the importance of this topic have evaluated the EI level in nursing students and indicated that variability exists in the EI levels of nursing students in various nations and cultural contexts. While few studies have reported low levels of EI (Fakhry & El-Azeem, 2016 ; Faye et al, 2011 ), the research majority found moderate to high EI levels (Albagawi, 2018 ; Almegewly et al, 2022 ; Beauvais et al, 2011 ; Mahmoud et al, 2013 ). The observed variability can be attributed to individual characteristics, cultural values, and educational system variations.…”
Section: Introductionmentioning
confidence: 99%